Building a sustainable future: perspectives on primary school sustainability projects from teachers and pre-service teachers - Ölçer-Çevik, Sena; Kozaner, Çiğdem (Institute of Advanced Engineering and Science, 2025)
Teachers play a critical role in implementing sustainable development education in the classroom and fostering sustainability awareness among students. The foundational knowledge and skills gained at the primary level help students develop sustainable practices and become environmentally conscious individuals. This study examines the experiences and perspectives of primary school teachers and pre-service teachers regarding sustainable development projects at the primary level, providing a qualitative, in-depth look at the feasibility and impact of sustainability education in classrooms. Insights were gathered from 52 participants (40 pre-service teachers with course experience in “sustainable development and education” and 12 primary teachers) using a phenomenological design. Findings show that pre-service teachers primarily used students’-based methods such as group work, brainstorming, and drama supported by mostly Web 2.0 tools and visuals, evaluating learning outcomes with pre and post-tests. However, they faced challenges in engaging students, accessing materials, and funding. Notably, sustainable development projects were found to enhance sustainability awareness in teachers and students while promoting global citizenship and critical thinking skills. These findings, consistent with literature, underscore the role of sustainable development education in fostering social awareness and competency development, offering strategic insights to improve its classroom implementation and the effectiveness of teachers’ contributions.